Effects of state cigarette excise taxes and smoke-free air policies on state per capita alcohol consumption in the U.S., 1980–2009 - Krauss, Melissa J. (2014)
BACKGROUND: Increasing state cigarette excise taxes and strengthening smoke-free air laws are known to reduce smoking prevalence. Some studies suggest that such policies may also reduce alcohol use, but results for cigarette taxes have been mixed and associations with smoke-free air policies have been limited to some demographic subgroups. To shed further light on the potential secondary effects of tobacco control policy, we examined whether increases in cigarette taxes and strengthening of smoke-free air laws were associated with reductions of per capita alcohol consumption and whether any reductions were specific to certain beverage types. METHODS: State per capita alcohol consumption from 1980–2009 was modeled as a function of state price per pack of cigarettes and smoke-free air policy scores while controlling for secular trends and salient state covariates. Both policy measures also accounted for local policies. Total alcohol, beer, wine, and spirits consumption per capita were modeled separately. For each type of beverage, we used a nested models approach to determine whether the two policies together were associated with reduced consumption. RESULTS: For total alcohol consumption, and for beer or spirits (but not wine), one or both tobacco policies were associated with reductions in consumption. A one percent increase in cigarette price per pack was associated with a 0.083% decrease in per capita total alcohol consumption (95% confidence interval [CI] 0.0002% to 0.166%, p=.0495), and a one point increase in SFA policy score, measured on a 6-point scale, was associated with a 1.1% decrease in per capita total alcohol consumption (95% CI 0.4% to 1.7%, p=.001; p<.001 for the hypothesis that the two policies are jointly associated with reduced alcohol consumption). CONCLUSIONS: The public health benefits of increasing cigarette taxes and smoke-free policies may go beyond the reduction of smoking and extend to alcohol consumption, specifically beer and spirits.